Nilai Toleransi Beragama Dalam Buku PABP Dan Implementasinya Di SMK Mardiyuana Cikembar Kabupaten Sukabumi - Nugraha, Iqbal Purwa; Zamroni, M. Afif; Katiko, Ari (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
This research examines the implementation of religious tolerance values ??in the Religious and Character Education (PABP) book and its practice at Mardi Yuana Vocational School, Cikembar. With a qualitative case study approach, this research collects data through participant observation, in-depth interviews, and documentation studies. The research results show that the values ??of religious tolerance, such as recognition of religious freedom, harmony between religious believers, mutual love and security, have been implemented well in the school environment. The PABP curriculum and school policies are important for instilling these values. Implementing religious tolerance values ??at Mardi Yuana Cikembar Vocational School is supported by various factors, such as government strategies, adequate facilities and infrastructure, support from all school members, availability of supporting books, and conducive environmental conditions. However, challenges and obstacles exist, such as the lack of written regulations prohibiting discrimination between religious believers and limited space for religious laboratories. This research provides recommendations for improving the PABP curriculum, increasing teacher competency, more effective learning strategies, and active involvement of all stakeholders. By comprehensively integrating the principles of multicultural education, Vocational School Mardi Yuana Cikembar can contribute significantly to creating a young generation that appreciates diversity and is committed to maintaining national unity